2021
DOI: 10.1016/j.jjcc.2020.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of antihypertensive drugs with the risk and severity of COVID-19: A meta-analysis

Abstract: Highlights The usage of antihypertensive drugs is not associated with the risk and severity of COVID-19. Hypertensive patients with COVID-19 benefit from prior usage of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 47 publications
3
78
0
2
Order By: Relevance
“…The authors investigated each of five antihypertensive classes separately. Similar results were reported in a large meta-analysis that included 2,100,587 participants ( 32 ). The investigators observed no association between prior usage of antihypertensive medications, including ACEIs/ARBs, calcium channel blockers, beta-blockers, or diuretics, and the risk or severity of COVID-19.…”
Section: Antihypertensive Therapy In Covid-19supporting
confidence: 88%
“…The authors investigated each of five antihypertensive classes separately. Similar results were reported in a large meta-analysis that included 2,100,587 participants ( 32 ). The investigators observed no association between prior usage of antihypertensive medications, including ACEIs/ARBs, calcium channel blockers, beta-blockers, or diuretics, and the risk or severity of COVID-19.…”
Section: Antihypertensive Therapy In Covid-19supporting
confidence: 88%
“…Promptly, in the first weeks of May, three large epidemiological studies were published supporting the lack of association between the outpatient use of RASIs and risk of COVID-19 [4-6]. Later on, a plethora of studies and meta-analyses were published [7,8] reaching the same conclusion, which provide reassurance on the safety of these drugs. Yet, the extent of RASI discontinuation at hospital admission during the first wave of the pandemic and, importantly, its impact on health outcomes have been scarcely studied [9-12].…”
Section: Introductionmentioning
confidence: 99%
“…New evidence since the publication of our original review includes results from a randomized controlled trial and 4 large database studies that included patients with a mix of disease severity ( 16–19 , 23 ). These studies consistently found that ACEI or ARB use was not associated with a higher risk for SARS-CoV-2 infection, findings which are further supported by 5 systematic reviews or meta-analyses ( 11 , 14 , 92–94 ). Because we consider these findings to be stable (meaning that future studies are likely to have the same results), we will no longer do literature surveillance on this KQ and will retire it from our living review.…”
Section: Key Question 1: Does the Use Of Aceis And Arbs Before Infectmentioning
confidence: 59%
“…These studies are all relevant to key question (KQ) 2 about the association of angiotensin-converting enzyme inhibitor (ACEI) or angiotensin-receptor blocker (ARB) use and coronavirus disease 2019 (COVID-19) severity, and they support our prior conclusion that ACEI or ARB use is not associated with a higher risk for severe COVID-19 illness. Two systematic reviews also address KQ1, adding support to our prior conclusion that ACEI or ARB use is not associated with an increased risk for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection ( 11 , 14 ).…”
mentioning
confidence: 72%